Олимпиадная информатика как способ формирования профессиональной компетентности учителя информатики в области программирования - Цыганова, А.Д. (My University, 2016)
The article deals with the formation of the professional competence of the teacher of computer science in the field of programming. One solution to the question is the study of methods for solving Olympiad nonstandard logical tasks of high complexity. The author considers a method of optimization the algorithm for solving tasks such as tasks of exhaustive search. This method is a method of algorithms on graphs.
Keywords: the methods for solving Olympiad tasks; algorithm; tasks of exhaustive search; algorithms on graphs